Tributação e financiamento dos direitos fundamentais : a promoção de políticas públicas por meio da tributação - Gesto, Martin da Silva (2016)
In this work it will be analyzed the taxation as a source of financing of the fundamental rights, besides of promoter of public policies. Beyond the systematic analysis of the taxation, it must prevail the idea that there is a constitutional conception of the taxes, for this reason, it can not be considered a simple exchange for the public services between the State and the citizens. Taxes can not be considered a citizens sacrifice. In name of the globalization and the modernity, many conceptions must be review, including the way that the taxation happens. The complexity that it imposes make emerge a new taxation, focused not only to generate revenue, although that this purpose still exists, because the taxation is necessary for the financing of the fundamental rights. However, it is essential that the taxation promote public policies beyond the extrafiscal taxation, focused on the long term results, as truly policies of State, not just policies of Government. The taxation can not be just a simple way of to create wealth to the State, being necessary that exists a clear harmony between the subjects of tax, financial, administrative and constitutional law, making possible the study supradisciplinary of taxation, because only doing this that the fundamental rights will be able to be implemented.